Internet of Things (IoT) Development Strategy to Improve SMEs in the Tourism Sector - Sulthana Nabila Yumna; Saputri Diva Eka; Candrakanta Athaya; Janah Roikhatul; Windriani; Aulia Rizka Dwi (SHS Web of Conferences)
Technological innovation is crucial in advancing the industry, including the tourism industry. Both to open new opportunities and to provide more efficient and effective services. The convergence of technology that occurs through the use of digitization of information is termed the Internet of Things (IoT). These significant challenges include resistance to change and limited infrastructure. Then how is the development strategy. The purpose of this study is to analyze the development strategy of IoT-based digital transformation in answering these challenges. The approach used in this research is a qualitative approach through literature study and content analysis. This research is a descriptive research. The results show that SMEs need to improve technology training to develop digital skills to be more effective and efficient. Strategies that can improve SMEs in the tourism sector with the adoption of IoT technology include the utilization of applications that support UGC, improve digital infrastructure, and switch to data-based marketing so that the adoption of IoT can be done effectively to improve the competitiveness and efficiency of SME businesses.